Observation of magnonic spin-orbit torque in epitaxial Co films - Tong Li; Yu Miao; Pei Liu; Yang Cao; Ze Yan; Yuzhi Li; Quanzhi Zhang; Cunxu Gao; Desheng Xue; Dezheng Yang (npj Spintronics)
Abstract Using spin-orbit torque (SOT) to manipulate magnons has played a crucial role in magnon spintronics. However, the contribution of magnons to the second harmonic voltage —critical for the calibration of SOT— remains elusive in spintronics. Here, we report the observation of magnon-induced SOT in an epitaxial Co film through precise low-magnetic-field measurements of second harmonic voltages in both longitudinal and transverse directions. Unlike the conventional field-like SOT, which operates independently of the magnetic field, the magnonic SOT exclusively emerges at low magnetic fields and undergoes rapid decay as the magnetic field increases. Our analysis reveals a significant linear correlation between the field-dependent decay of the observed SOT and the magnon-induced unidirectional magnetoresistance effect. This correlation provides compelling evidence that magnons drive the observed SOT.